External validity of the T-SAFT90: A soccer simulation including technical and jumping activities - da Silva, C. D.; Lovell, R. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the physiological, muscle-damage, endocrine, and immune responses to a modified soccer-simulation protocol to include technical and jumping activities characteristic of match play (the Technical Soccer-Specific Aerobic Field Test; T-SAFT90). Methods: Eighteen university players (age 23 [2] y, stature 175 [5] cm, body mass 74 [11] kg) performed the 90-minute protocol, with acute physiological responses monitored via heart rate, ratings of perceived exertion (6-20 scale), and body mass changes. Creatine kinase, myoglobin, cortisol, and leukocyte subset concentrations were measured at baseline, immediately (0 h), and 24 hours post T-SAFT90. Results: T-SAFT90 incurred an average heart rate equivalent to 87% (5%) of maximum, 16 (2) a.u. ratings of perceived exertion, and a 1.5% (1.0%) body mass deficit. Moderate to large proliferation of leukocyte subsets (P=.01; leukocytes: 6.4-fold; neutrophils: 5.5-fold; lymphocytes: 2.0-fold) and increases in cortisol (2.3-fold) were observed at 0 hours (effect size=1.13-3.52), each returning to baseline by 24 hours (P>.45; effect size=0.05-0.50). Myoglobin peaked immediately post T-SAFT90 (4.8-fold), whereas creatine kinase (24 h: 6.0-fold) showed a delayed time course (both P=.001; very large effects; effect size=2.66 and 3.43, respectively). Conclusions: The magnitude and time course of the physiological, immune, endocrine, and muscle-damage markers observed during and following T-SAFT90 are similar to values reported in match-play literature, demonstrating external validity of the simulation.